Palynology of the Triassic - Jurassic of the Silves group in Portugal - its implications on a changing world - Boas, Ana Margarida Silva Vilas (2024)
The biostratigraphy of the Lusitanian and Algarve basins is based on macrofossils and microfossils (foraminifers, nannofossils, and ostracods). Compared to these works, palynological studies are rare in these basins. Palynomorphs are a powerful biostratigraphic and paleoenvironmental tool, and their research could significantly contribute to the context of the two basins. In this project, the Upper Triassic and Lower Jurassic of the Lusitanian and Algarve basins were studied. In the Lusitanian Basin, twelve sections were sampled, all in Coimbra and Miranda do Corvo: Lamas I, Lamas II, Castelo Viegas I, Castelo Viegas II, IdealMed, Alto de São João, Parque de Campismo, Sobral Cid, Carvalhais, Redonda, Lordemão and Eiras. A total of 122 samples were collected in these sections and studied in detail. In the Algarve Basin, fifteen sections were sampled throughout the entire basin: Vale de Fuzeiros, Bengado, International Racetrack of Algarve, Marco, Loulé Rock Salt Mine, Santa Rita, Amorosa, Amado’s Beach, Rocha da Pena, Bodega, Barragem do Funcho, Santa Catarina Fonte do Bispo, Fonte da Pedra, Diapiro de Albufeira and Ayamonte. Full amount of 254 samples were collected in these sections and studied in detail. (...)